基于传力特性的2RPR冗余机构优化设计 - 赵辉; 张春凤; 杨宝刚 (Jixie chuandong)
The traditional design index isn’t proper to be used directly to design the redundant mechanism in some situations,and so there are some difficulties to design.A new design index to descript the force transmission characteristics of a redundant mechanism is proposed based on the transmission angle.Then a 2RPR redundant mechanism is optimal designed with the design index.It’s an efficient method and has a certain reference to design a redundant mechanism.